Substantially improved room temperature NO2 sensing in 2-dimensional SnS2 nanoflowers enabled by visible light illumination. Issue 18 (9th April 2021) - Eom, Tae Hoon; Cho, Sung Hwan; Suh, Jun Min; Kim, Taehoon; Lee, Tae Hyung; Jun, Sang Eon; Yang, Jin Wook; Lee, Jongwon; Hong, Seong-Hyeon; Jang, Ho Won
Abstract : The enriched edge sites of SnS2 NFs substantially improve the gas sensing properties under visible light illumination. Abstract : 2-Dimensional semiconductor SnS2 has emerged as one of the most prospective candidates for chemoresistive gas sensor applications due to its outstanding gas sensing performance. Herein, we propose the room temperature nitrogen dioxide (NO2 ) sensing of SnS2 nanoflowers (NFs) enabled by visible light activation. SnS2 NFs were successfully prepared by solvothermal synthesis with abundant edge sites. The high absorbance in the visible light region triggered the generation of charge carriers resulting in decreased resistance and enhanced gas sensing characteristics. Even under red light and green light with low photon energy, the room temperature NO2 sensing performance was improved. The highest NO2 sensing performance was accomplished under blue light, including the highest response, excellent selectivity towards NO2 and an extremely low detection limit. Moreover, the sensor exhibited reliable gas sensing performance in humid conditions and maintained its properties after long-term relaxation. Taking advantage of surface properties, optical properties and gas sensing properties, a light-activated SnS2 NF based gas sensor is anticipated to further develop SnS2 nanostructures for use in an electronic nose.